An occupational perspective of poverty and poverty reduction. Issue 2 (3rd April 2017) - Sofo, Francesco; Wicks, Alison
ABSTRACT: Poverty is a complex problem with diverse interdependencies. Effective poverty reduction requires new ways of thinking about poverty and innovative programs to reduce its impact on people, communities and the environment. To date, a mix of economic, social structural, capabilities and learning perspectives have been applied to understanding poverty and planning strategies to expedite its reduction. We propose that inclusion of an occupational perspective will foster deeper understanding of the causes of poverty and its impact on people and communities. To that end, we introduce the SEED-SCALE, a novel theoretical framework designed to bring about social change. We argue that it is inherently occupation-focused and highly appropriate for poverty reduction programs, as it uses human energy (i.e. what humans do) to generate community and global solutions.